THE EFFECT OF SOCIAL SUPPORT AND SPIRITUAL INTELLIGENCE ON THE NURSES ANXIETY LEVEL OF “IS” HOSPITAL PEKANBARU DURING COVID-19 PANDEMIC - Anov Satria Pamungkas; Nurul Hidayah; Siti Urbayatun (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2020)
COVID 19th pandemic situation adversely affect every aspect of life, not excluding the nursing professionwho are at the forefront of dealing with patients affected by COVID-19. This causes nurses to experiencestress, depression and anxiety due to increased work demands. This study aims to determine the effect ofsocial support and spiritual intelligence on the anxiety level of nurses in the hospital. The subjects in this studywere 87 nurses at the “IS” Hospital Pekanbaru. The sampling technique used in this study was purposivesampling technique. The instruments used were the COVID-19 Intelligence scale, the Social Support scale,and the Spiritual Intelligence scale. The data analysis technique used is multiple linear regression analysis. Theresults of the data analysis showed that F = 10.531 with a value of p = 0.000 (p <0.01) indicated that there wasa very significant influence between social support and spiritual intelligence on nurses' intelligence. Theresults of further analysis with a partial value = -0.254. p = 0.018 (p <0.05) indicates a significant negativeeffect between social support and anxiety. The results of further analysis with a partial value = -0.215. p =0.047 (p <0.05) indicates a significant negative effect between spiritual intelligence and anxiety. Based onthese results, it can be concluded that there is a very significant negative effect of social support and spiritualintelligence on nurse anxiety. This means that the higher the social support and spiritual intelligence that isowned, the level of anxiety will be lower and behave harshly